Editorial - Alam, AHM Zahirul (IIUM Engineering Journal, 2018)
<!-- [if !mso]> <![endif]--><!-- [if gte mso 9]> <![endif]--> IIUM ENGINEERING JOURNAL CHIEF EDITOR Ahmad Faris Ismail, IIUM, Malaysia TECHNICAL EDITOR Erry Yulian Triblas Adesta, IIUM, Malaysia EXECUTIVE EDITOR AHM Zahirul Alam, IIUM, Malaysia ASSOCIATE EDITOR Anis Nurashikin Nordin, IIUM, Malaysia LANGUAGE EDITOR Lynn Mason, Malaysia COPY EDITOR Hamzah Mohd. Salleh, IIUM, Malaysia EDITORIAL BOARD MEMBERS Abdullah Al-Mamun, IIUM, Malaysia Abdumalik Rakhimov, IIUM, Malaysia Amir Akramin Shafie, IIUM, Malaysia Erwin Sulaeman, IIUM, Malaysia Hanafy Omar, Saudi Arabia Hazleen Anuar, IIUM, Malaysia Konstantin Khanin, University of Toronto, Canada Ma'an Al-Khatib, IIUM, Malaysia Md Zahangir Alam, IIUM, Malaysia Meftah Hrairi, IIUM, Malaysia Mohamed B. Trabia, United States Mohammad S. Alam, Texas A&M University-Kingsville, United States Muataz Hazza Faizi Al Hazza, IIUM, Malaysia Mustafizur Rahman, National University Singapore, Singapore Nor Farahidah Binti Za'bah, IIUM, Malaysia Ossama Abdulkhalik, Michigan Technological University, United States Rosminazuin AB. Rahim, IIUM, Malaysia Waqar Asrar, IIUM, Malaysia AIMS & SCOPE OF IIUMENGINEERING JOURNAL The IIUM Engineering Journal, published biannually, is a carefully refereed international publication of International Islamic University Malaysia (IIUM). Contributions of high technical merit within the span of engineering disciplines; covering the main areas of engineering: Electrical and Computer Engineering; Mechanical and Manufacturing Engineering; Automation and Mechatronics Engineering; Material and Chemical Engineering; Environmental and Civil Engineering; Biotechnology and Bioengineering; Engineering Mathematics and Physics; and Computer Science and Information Technology are considered for publication in this journal. Contributions from other areas of Engineering and Applied Science are also welcomed. The IIUM Engineering Journal publishes contributions under Regular papers, Invited review papers, Short communications, Technical notes, and Letters to the editor (no page charge). Book reviews, reports of and/or call for papers of conferences, symposia and meetings, and advances in research equipment could also be published in IIUM Engineering Journal with minimum charges. REFEREES’ NETWORK All papers submitted to IIUM Engineering Journal will be subjected to a rigorous reviewing process through a worldwide network of specialized and competent referees. Each accepted paper should have at least two positive referees’ assessments. SUBMISSION OF A MANUSCRIPT <!-- [if gte vml 1]> <![endif]--><![if !vml]> <![endif]>A manuscript should be submitted online to the IIUM-Engineering Journal website: http://journals.iium.edu.my/ejournal. Further correspondence on the status of the paper could be done through the journal website and the e-mail addresses of the Executive Editor: zahirulalam@iium.edu.my Faculty of Engineering, International Islamic University Malaysia (IIUM), Jan Gombak, 53100, Kuala Lumpur, Malaysia. Phone: (603) 6196 4529, Fax:(603) 6196 4488. INTERNATIONAL ADVISORY COMMITTEE A. Anwar, United States Abdul Latif Bin Ahmad, Malaysia Farzad Ismail, USM, Pulau Pinang, Malaysia Hanafy Omar, Saudi Arabia Hany Ammar, United States Idris Mohammed Bugaje, Nigeria K.B. Ramachandran, India Kunzu Abdella, Canada Luis Le Moyne, ISAT, University of Burgundy, France M Mujtaba, United Kingdom Mohamed AI-Rubei, Ireland Mohamed B Trabia, United States Mohammad S. Alam, Texas A&M University-Kingsville, United States Nazmul Karim Ossama Abdulkhalik, Michigan Technological University, United States Razi Nalim, IUPUI, Indianapolis, Indiana, United States Syed Kamrul Islam, United States Tibor Czigany, Budapest University of Technology and Economics, Hungary Yiu-Wing Mai, The University of Sydney, Australia. Published by: IIUM Press, International Islamic University Malaysia Jalan Gombak, 53100 Kuala Lumpur, Malaysia Phone (+603) 6196-5014, Fax: (+603) 6196-6298 Website: http://iiumpress.iium.edu.my/bookshop Whilst every effort is made by the publisher and editorial board to see that no inaccurate or misleading data, opinion or statement appears in this Journal, they wish to make it clear that the data and opinions appearing in the articles and advertisement herein are the responsibility of the contributor or advertiser concerned. Accordingly, the publisher and the editorial committee accept no liability whatsoever for the consequence of any such inaccurate or misleading data, opinion or statement. IIUM Engineering Journal ISSN: 1511-788X E-ISSN: 2289-7860 Volume 19, Issue 1, June 2018 https://doi.org/10.31436/iiumej.v19i1 Table of Content CHEMICAL AND BIOTECHNOLOGY ENGINEERING ADSORPTION OF HEAVY METALS AND RESIDUAL OIL FROM PALM OIL MILL EFFLUENT USING A NOVEL ADSORBENT OF ALGINATE AND MANGROVE COMPOSITE BEADS COATED WITH CHITOSAN IN A PACKED BED COLUMN... 1 Rana Jaafar Jawad, Mohd Halim Shah Ismail, Shamsul Izhar Siajam INVESTIGATION OF BIOFLOCCULANT AS DEWATERING AID IN SLUDGE TREATMENT........................................ 15 Mohammed Saedi Jami, Maizirwan Mel, Aysha Ralliya Mohd Ariff, Qabas Marwan Abdulazeez HYDROGEN PRODUCTION FROM ETHANOL DRY REFORMING OVER LANTHANIA-PROMOTED CO/AL2O3 CATALYST............................. 24 Fahim Fayaz, Nguyen Thi Anh Nga, Thong Le Minh Pham, Huong Thi Danh, Bawadi Abdullah, Herma Dina Setiabudi, Dai-Viet Nguyen Vo OPTIMIZATION OF RED PIGMENT PRODUCTION BY MONASCUS PURPUREUS FTC 5356 USING RESPONSE SURFACE METHODOLOGY......................................................... 34 Nor Farhana Hamid And Farhan Mohd Said PRODUCTION AND STABILITY OF MYCO-FLOCCULANTS FROM LENTINUS SQUARROSULUS RWF5 AND SIMPLICILLIUM OBCLAVATUM RWF6 FOR REDUCTION OF WATER TURBIDITY.............................................................................. 48 Nessa Jebun, Md. Zahangir Alam, Abdullah Al-Mamun, Raha Ahmad Raus ROLE OF SUBSTRATE BINDING ON THE PROTEIN DYNAMICS OF AN ENDOGLUCANASE FROM FUSARIUM OXYSPORUM AT DIFFERENT TEMPERATURES .............................................................307 Abdul Aziz Ahmad, Ibrahim Ali Noorbatcha, Hamzah Mohd. Salleh CIVIL AND ENVIRONMENTAL ENGINEERING DIMINISHING SEISMIC EFFECT ON BUILDINGS USING BEARING ISOLATION....................................................... 59 A. B. M. Saiful Islam ELECTRICAL, COMPUTER AND COMMUNICATIONS ENGINEERING A DISTRIBUTED ENERGY EFFICIENT CLUSTERING ALGORITHM FOR DATA AGGREGATION IN WIRELESS SENSOR NETWORKS.................................................................................. 72 Seyed Mohammad Bagher Musavi Shirazi, Maryam Sabet, Mohammad Reza Pajoohan POWER QUALITY IMPROVEMENT WITH CASCADED MULTILEVEL CONVERTER BASED STATCOM................. 91 Mahdi Heidari, Abdonnabi Kovsarian, S. Ghodratollah Seifossadat THE EFFECTS OF CABLE CHARACTERISTICS ON MAXIMUM OVERVOLTAGE IN COMBINED OVERHEAD/CABLE LINES PROTECTED BY SURGE ARRESTERS.............................................................................. 104 Reza Alizadeh, Mohammad Mirzaie SMART PORTABLE CRYOTHERAPY SYSTEM REPHRASED I.E. WITH CONTROLLED THERMOELECTRIC COOLING MODULES FOR MEDICAL APPLICATIONS................................................................................................ 117 Abbas Rahmani, Reza Hassanzadeh Pack Rezaee, Naser Kordani STATIC PIPELINE NETWORK PERFORMANCE OPTIMISATION USING DUAL INTERLEAVE ROUTING ALGORITHM 129 Siva Kumar Subramaniam1, Shariq Mahmood Khan, Anhar Titik, Rajagopal Nilavalan A MODIFIED MODEL BASED ON FLOWER POLLINATION ALGORITHM AND K-NEAREST NEIGHBOR FOR DIAGNOSING DISEASES........................................................................ 144 Mehdi Zekriyapanah Gashti A SINGLE LC TANK BASED ACTIVE VOLTAGE BALANCING CIRCUIT FOR BATTERY MANAGEMENT SYSTEM .158 A K M Ahasan Habib, S. M. A. Motakabber, Muhammad Ibn. Ibrahimy, A. H. M. Zahirul Alam ENGINEERING MATHEMATICS AND APPLIED SCIENCE ON THE CONTROL OF HEAT CONDUCTION.......................................... 168 Fayziev Yusuf Ergashevich MATERIALS AND MANUFACTURING ENGINEERING GREEN SYNTHESIS OF SILVER NANOPARTICLES USING SAGO (METROXYLON SAGU) VIA AUTOCLAVING METHOD......178 Aliyah Jamaludin, Che Ku Mohammad Faizal EFFECT OF ALKALINE TREATMENT ON PROPERTIES OF RATTAN WASTE AND FABRICATED BINDERLESS PARTICLEBOARD....185 Zuraida Ahmad, Maisarah Tajuddin, Nurul Farhana Fatin Salim, Zahurin Halim AMORPHOUS STRUCTURE IN CU-ZN-V-AL OXIDE COMPOSITE CATALYST FOR METHANOL REFORMING..... 197 Mohd Sabri Mahmud, Zahira Yaakob, Abu Bakar Mohamad, Wan Ramli Wan Daud, Vo Nguyen Dai Viet PERFORMANCE OF ELECTRICAL DISCHARGE MACHINING (EDM) WITH NICKEL ADDED DIELECTRIC FLUID....215 Ahsan Ali Khan, Muataz Hazza Faizi Al Hazza, A K M Mohiuddin, Nurfatihah Abdul Fattah, Mohd Radzi Che Daud ENVIRONMENTAL DEGRADATION OF DURIAN SKIN NANOFIBRE BIOCOMPOSITE.......................................... 233 Siti Nur E’zzati Mohd Apandi, Hazleen Anuar, Siti Munirah Salimah Abdul Rashid MECHANICAL AND AEROSPACE ENGINEERING A REVIEW ON RHEOLOGY OF NON-NEWTONIAN PROPERTIES OF BLOOD....................................................... 237 Esmaeel Fatahian, Naser Kordani, Hossein Fatahian NUMERICAL STUDY OF THERMAL CHARACTERISTICS OF FUEL OIL-ALUMINA AND WATER-.......................... 250 Hossein Fatahian, Hesamoddin Salarian, Majid Eshagh Nimvari, Esmaeel Fatahian A PARAMETRIC STUDY ON CONTROL OF FLOW SEPARATION OVER AN AIRFOIL IN INCOMPRESSIBLE REGIME....270 Lakshmanan Prabhu, Jonnalagadda Srinivas OPTIMIZATION OF BOX TYPE GIRDER WITH AND WITHOUT INDUSTRIAL CONSTRAINTS................................ 289 Muhammad Abid, Shahbaz Mahmood Khan, Hafiz Abdul Wajid